Imaculada Concepción: A construção de imagens-corpos femininos em La Femme et le Pantin - Edoardo, Laysmara Carneiro (2010)
This study is focus for reflection on the construction of the female body within a few fictional forms that refer to different aesthetic elaborations of the image. Since the literary narrative also says descriptions of the image of characters, environments and psychological states, took up the character Conchita, the novel La femme et le Pantin (1898), written by Pierre Louÿs, in an attempt to discuss the different representations of the female , resorting to mythology, painting, cinema and photography, mediated by the iconography and iconology, as well as key-caraters in the ocidental imaginary, arguing that such representations are part of the building imagery, not only the body, as also of desire and seduction. In this sense, the relationships between the filmic translations of the novel - The Devil Is a Woman (Von Sternberg, 1935), La femme et le Pantin (Duvivier, 1959) and Cet obscure object du désir (Buñuel, 1977) - and the interpretations of the context of the literary work of Louÿs, also refer to Lacan's psychoanalytic scholia and schizo-analytical Deleuze and Guattari, in order to problematize the affinities and incursions of desire within the representations of the female during the time covered in this work.